The quality of industrially manufactured medicines in Spain between 1850 and 1950. Review of the quality requirements for the authorisation of medicines during this period - Buhigas Cardó, MR; Suñé Negre, JM; Bel Prieto, E (Ars Pharmaceutica (Internet), 2012)
Objectives: The aim is to study the evolution of quality requirements in the application file for approval of drug products and their relationship with the quality of industrially manufactured drugs between 1850 and 1950, taking into account the influence of political and social context. Materials and methods: Analysis of the legislation published in Spain referring to pharmaceutical registration from 1850 to 1950, comparing the quality benchmarks to highlight the improvement. Search of information in journals and unpublished documents. Discussion on quality progress related to the socio-political context of the country. Results and conclusions: Until 1855 drugs did not exist as such, there were only secret remedies. The Law of November 28, 1855 established the obligation to declare the remedies to the Health Authority. Since then there was an evolution until the Royal Decree of 1919 established the official register of medicines and assigned a registration number to each medicine. The Royal Decree of 1924 updated the 1919 Decree but no advance was done referring to quality. Then a period of stagnation followed in both the rules of registration and the quality due to the civil war and the international blockade. A Law Reform was announced in 1944 but it took a long time to be done. Summarizing: It was a long period, with advances in organization and little progress in quality requirements in the pharmaceutical registration. When quality requirements increased, drug quality also did. Application files for registration are an essential reference to know the quality at some time.